Understanding the counselling relationship - Feltham, Colin (London : Thousand Oaks, Calif. : SAGE Publications, 1999)
Written for those involved in counselling, this book presents the contrasting views of a range of practitioners about the therapeutic relationship. They each consider the relational variables that have most bearing on the practice of therapy.
Includes bibliographical references and index.
Keywords: Counselor and client; Counseling; Psychology -- Psychotherapy -- Counseling